Innovation supports for small-scale development in rural regions: a create, build, test and learn approach. (2nd April 2020) - Lugnet, Johan; Ericson, Åsa; Wenngren, Johan
Small and medium sized firms' businesses in rural regions typically address a home market and the delivery of niched products. This makes them exposed to business downturns, innovation is thus one way to survive and prosper. Small-scale product development is typically very hands-on, a sort of trial and error process. This experimental way is in favour for the implementation of innovation processes, but one challenge is the limited resources that firms can, or are willing to, spend on innovative work. A challenge is that procedures for organisational learning are lacking in the straightforward approach. The article describes the background and rationale for supporting small-scale manufacturing by introducing a support toolbox for early product development work. The support toolbox's rationale is built upon learning cycles and communicative prototyping which may enhance innovation process capabilities.